RUOLO E COMPETENZE DEGLI EFETI DA DRACONTE ALL’ETÀ DEGLI ORATORI (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2013)
The author presents the results of a study on the ephetai investigating theirrole, jurisdiction and selection in the overall framework of the Athenian homicidecourts. In the period between Drakon and Solon, only the Areopagos, the Prytaneionand the 51 ephetae (who were at that time chosen among the Areopagites)tried homicide cases. Only after Solon two new homicide courts were instituted:the Delphinion and the court “in Phreatto”. The 51 ephetae never took part tothese last two courts, whose judges were chosen by lot from the heliastai. In thefifth and fourth centuries BC, also the 51 ephetae (who at that time gathered at thePalladion) started to be chosen by lot, probably from the heliastai as well.In questo studio l’autore offre una disamina del ruolo, delle competenze eanche della composizione del collegio giudicante degli efeti nel quadro complessivodei tribunali ateniesi per l’omicidio. Nel periodo compreso tra Draconte eSolone, erano competenti per l’omicidio solo l’Areopago, il Pritaneo e i 51 efeti(scelti tra gli areopagiti). Solo dopo Solone comparvero due nuovi tribunali, Delfinioe Freatto. I 51 efeti non furono mai presenti in questi ultimi due tribunali,in cui si riunivano eliasti estratti a sorte. Tra quinto e quar to secolo a.C., anche i51 efeti (che a quel tempo si riunivano al Palladio) iniziarono a essere estratti asorte, probabilmente anch’essi tra gli eliasti.